Phenomenology of the Queer Teory: Culture, Identity And Spirit - Cedeño Astudillo, Luis Fernando (Universidad del Zulia, 2020)
The gender approach is much more than a simple discursive perception. While tolerance and respect play an important role in the prevention of violence and any form of gender discrimination, it does not mean that cultural factors are the only predominant issues in this subject of study, as the queer theory, the strange, the weird, lately it has become the favorite excuse to reject everything that opposes gender as a construction.